MOOD TYPES OF DONALD TRUMP’S SPEECH IN THE ARAB ISLAMIC AMERICAN SUMMIT - Ajeng Rahayu; Hanafi Bilmona (CALL, 2021)
This research deals with analyzing language from the perspective of Systemic Functional Linguistics (SFL) from Donald Trump’s speech in the Arab Islamic American Summit. In English, one of types of meaning is Interpersonal meaning. It is realized by mood and modality. This research focuses on mood, then formulated into two research questions: 1) What mood types are used in Donald Trump’s speech in the Arab Islamic American summit? 2) What mood adjuncts are used in Donald Trump’s speech in the Arab Islamic American Summit?. The method used in this research is qualitative research. The source of data is the video of Donald Trump’s speech from Youtube. It was taken from (CNN, 2017) to get the transcript of speech by Donald Trump. It was found that there were 355 clauses in Donald Trump’s speech; there were 4 types of mood in the speech of Donald Trump; there were 337 declaratives mood with percentage 94.92%, 4 Polar-Interrogatives mood with percentage 1.12%, 4 WH-Interrogatives mood with percentage 1.12% and 10 imperatives mood with percentage 2.25%. Declarative as the most dominant types of mood is used in Donald Trump’s, speech which means that he gave or stated information to the audiences. In addition, in Donald Trump’s speech, there are 19 clauses which contain mood adjunct. The findings indicated that there were 3 types of mood adjunct in the speech, namely, 5 adjuncts of modality with percentage 26.31%, 3 adjuncts of temporality with percentage 15.78%, and 11 adjuncts of intensity with percentage 57.89%. The most dominant is adjuncts of intensity which expresses expectation. Keywords: Systemic Functional Linguistics; Mood; Mood Adjunct